Peran Forum Pemuda Kerukunan Umat Beragama Daerah Istimewa Yogyakarta dalam Memperkuat Paradigma Inklusif Kaum Muda - Ahmadi, Makhrus (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2017)
AbstractReligious life in Yogyakarta (DIY) has its own style and culture. It is based on the existence of DIY as a student town, travel, and education, resulting in DIY is seen as civil of tolerance due to DIY into a meeting place for differences of race, culture and religion. Thus, the existence of this study want to study on the role, community leaders and the government's response to the Youth Forum for Religious Harmony Special Region of Yogyakarta (FPKUB DIY) in strengthening the inclusive paradigm among young people in Yogyakarta.This study used descriptive qualitative approach. While data collection techniques using the documentation, observation and interviews. Analysis of the data used in this research is data obtained and presented descriptively, begins by describing that has been expressed by the respondents either in person, in writing or direct observation. The process of data analysis is done by starting to examine all the data collected from various sources that had been predetermined.This study shows that DIY FPKUB role in strengthening the inclusive paradigm of youth done with emphasis on inter-religious dialogue and national harmony. Form of program activities carried out by FPKUB DIY using participatory-dialogical that program activities runs are varied and well targeted, it is shown by the responses of participants who stated that 25% strongly agree, 60% agree, 15% disagree, 0% no agree, while the expectations of participants towards FPKUB DIY activities are in accordance with the expectations and desires of the participants with the response indicated 5% strongly agree, 85% agree, 10% disagree, 0% disagreed. Response to the role of community leaders FPKUB DIY done by inserting a board representative FPKUB DIY into management FKUB DIY that became the highest forum forum inter-religious harmony that already exist in each district and town in the province. Moreover, historically the birth of an initiative FPKUB DIY community leaders to encourage their mutual awareness among young people about religious harmony, so hope the presence of a pilot program DIY FPKUB other regions in Indonesia regarding inter-religious harmony forum based youth. The government's role Yogyakarta Special Region in strengthening the paradigm of inclusive youth conducted by FPKUB DIY done by providing facilities and infrastructures for use in a variety of activities by FPKUB DIY, though related forms penyelediaan facilities on grants and funding programs could not be implemented due to the lack of legal protection FPKUB overshadow the existence of DIY.Keywords: paradigm, inclusive, youth, religious groups